Answer:
See answers below.
Explanation:
All of these use the same idea: multiply numerator and denominator by the conjugate radical (an identical expression but with the sign between terms changed).
![(1)/(13-√(15))\cdot(13+√(15))/(13+√(15))=(13+√(15))/(169-15)}\\\\=(13+√(15))/(154)](https://img.qammunity.org/2022/formulas/mathematics/high-school/t5mxzv38xc71bccov82oio21bpfpryy38s.png)
![(1)/(√(13)-√(11)) \cdot (√(13)+√(11))/(√(13)+√(11))=(√(13)+√(11))/(13-11)\\\\=(√(13)+√(11))/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/i28i6rvjwbnxzze2onz8pg0qg8osarcf13.png)
![(1)/(√(21)+√(29))\cdot(√(21)+√(29))/(√(21)+√(29))=(√(21)+√(29))/(21-29)\\\\=(√(21)+√(29))/(-8)](https://img.qammunity.org/2022/formulas/mathematics/high-school/qyng9rx1yz15vawh9oukd53jpjr5g6vulj.png)
Note: Here's an example of what happens when you multiply conjugate radicals.
![(√(13)-√(11)})(√(13)+√(11))=13-√(11)√(13)+√(13)√(11)-11=13-11](https://img.qammunity.org/2022/formulas/mathematics/high-school/6uqrytwds3v8rp3ctljh1x3r7gzrx9szc0.png)
When you FOIL those binomials, the square roots go away!